Return to Sports After Bone Marrow–Derived Cell Transplantation for Osteochondral Lesions of the Talus. (January 2017) - Vannini, Francesca; Cavallo, Marco; Ramponi, Laura; Castagnini, Francesco; Massimi, Simone; Giannini, Sandro; Buda, Roberto Emanuele
Objective: Arthroscopic "one-step" technique based on bone marrow–derived cell transplantation (BMDCT) have achieved good results in repairing osteochondral lesions of the talus (OLT), overcoming important drawbacks of older techniques. It may be particularly adequate for the treatment of athletes in order to permit a safe and stable return to sports. The aim of this study was to report the results at 48 months of a series of athletes and the factors influencing the return to sports. Design: Case series. A total of 140 athletes underwent a "one-step" BMDCT repair of OLT. All the patients had the cells harvested from the iliac crest, condensed and loaded on a scaffold, and then implanted. Patients were evaluated clinically by the American Orthopaedic Foot and Ankle Society (AOFAS) scores and Halasi score. Results: AOFAS score improved from 58.7 ± 13.5 preoperatively to 90.6 ± 8.6 ( P < 0.005) at 24 months, and to 90.9 ± 10.7 at 48 months. Halasi score was 6.88 ± 1.8 preinjury, 4.08 ± 1.7 preoperatively, and 5.56 ± 2.0 at final follow-up. At the final follow-up, all the patients (beside 1 failure and 3 lost) were able to return to activity and 72.8% were able to resume sports at preinjury level. Conclusions: "One-step" BMDCT repair of OLT had good clinical results that was durable over time in athletes, permitting a return to sports at preinjury level in the majority of patients. The preoperative presence of impingement and articular degeneration were the main negative prognostic factors.